The pattern is this:

You add the sides of the triangle and multiply the sum by -4 to get the inside number of the triangle.

Proof:

1st Triangle = 2-3-5 = -6 x -4 = 24

2nd Triangle = 6-1-2 = 3 x -4 = -12

3rd Triangle = 8-2-10 = -4 x -4 = 16

4th Triangle = 7 + 5 -4 = 8 x -4 = -32

They all check out.

Now we just apply this to the new triangles to determine the new numbers:

1st Triangle = 4 - 6 - 11 = -13 x -4 = 52

2nd Triangle = 11 - 3 - 8 = 0 x -4 = 0

3rd Triangle = 12 - 4 - 2 = 6 x -4 = -24

4th Triangle = 5 + 9 - 6 = 8 x -4 = -32

Thus 52, 0 , -24, and -32 are your new numbers.